The interplay of geology, climate and tectonics on river incision: the example of the High Verdon Gorges, Southwestern French Alps - Cardinal, Thibaut; Petit, Carole; Rolland, Yann; Schwartz, Stéphane; Valla, Pierre Gaston; Scalabrino, Bruno; Audin, Laurence; Bertauts, Maxime; Zerathe, Swann; Thiéblemont, Denis; Braucher, Régis; Team, ASTER (Comptes Rendus. Géoscience)
Deciphering the impact of short-term or long-term forcing on fluvial incision, as well as understanding the influence of local (channel lithology and morphology) and global (tectonic motions) parameters in the spatial variation of incision efficiency, are ongoing geomorphological research fields. To shed new light on these issues, we chose to study the “Hautes Gorges du Verdon” (High Verdon Gorges or HVG), located in the foreland of the Southwestern Alps. We collected 24 samples along three polished surfaces for Cosmic Ray Exposure (CRE) $^{36}$Cl dating, which allowed us to constrain short-term incision rates ranging from 0.06 to 0.2 mm/yr between 60 and 15 ka. Compared to known regional uplift and denudation rates, incision rates obtained in the HVG suggest tectonic or isostatic uplift as the main driver of Verdon River incision in the Late Quaternary. This comparison allows us to propose that the downcutting of the Verdon Gorges started approximatively 1.5 to 2 Ma ago, even if the drainage network of the Verdon catchment area could have been shaped earlier, during the Messinian salinity crisis.